The mechanism of electrochemical reduction of hydrogen peroxide on silver nanoparticles. Issue 3 (20th December 2017) - Cai, Xiaosheng; Tanner, Eden E. L.; Lin, Chuhong; Ngamchuea, Kamonwad; Foord, John S.; Compton, Richard G.
Abstract : Reduction of hydrogen peroxide on silver nanoparticle modified electrodes in the neutral solution proceeds through a CE mechanism. Abstract : The reduction of hydrogen peroxide on a silver nanoparticle modified boron doped diamond electrode in a neutral solution is shown to proceed through a CE mechanism. Hydrogen peroxide undergoes a disproportionation reaction to form oxygen (and water) on the silver surface, creating a diffusion layer of oxygen, which, at a sufficiently biased electrode, is then reduced to hydrogen peroxide. Voltammetry and a full mechanistic simulation are undertaken to confirm the mechanism, showing at short times a dependence of the reductive signal on waiting time prior to voltammetric analysis reflecting the extent of the disproportionation step which occurs prior to voltammetric analysis.